Better than nothing? a review and critique of child sponsorship (Research, Society and Development, 2020)
The aim of this paper is to review and synthesize research focused on child sponsorship (CS) and, in doing so, to present a critique grounded in conceptualizations of justice, solidarity, ethical relationships, and international development education.  As discussed in this paper, a review of the literature yields eight motivations for becoming involved in child sponsorship: Personal connection; altruism; guilt; small win; part of something bigger; distrust of government; not faceless; advancing development. Following the research synthesis and discussion of these motivations, a critique is constructed by viewing these motivations through three theoretical lenses: conceptualizations of the good citizen, the complex audience member and, finally, a pedagogical tool and framework referred to as HEADS UP. The paper concludes with questions centring on power, poverty, responsibility, complicity, justice and peace, and, ultimately, provides a response to the question of “is it better than nothing?” The argument put forth in this paper is that, in its noted absence of a more critical examination of the root causes of poverty and global injustices, child sponsorship is, in fact, not better than nothing.